Optimalisisai Potensi Peserta Didik: Tantangan Pendidik Indonesia dalam Pendidikan Berbasis Kompetensi - Widhanarto, Ghanis Putra; Prihatin, Titi; Haryono, Haryono; Kusumawardani, Seftia (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
Competency-based education (CBE) is an instructional model gaining popularity in schools. A preliminary study found that teachers' identities must shift to engage in CBE fully. They must construct classrooms engaging and supporting students in independent learning. This study aims to uncover teachers' understanding of CBE and implementation challenges. A quantitative descriptive research method used questionnaires distributed to 1,905 teachers across Indonesia. The results showed that teachers have a good grasp of CBE regarding learning standards, methods, media, strategies, assessment, and student involvement. Challenges included determining the achievement of learning objectives, assignment deadlines for students, and strategies for sharing experiences. Proper CBE implementation requires teacher readiness in skills and CBE understanding. Those challenges provide implications for quality competency-based learning and assessment in schools.